Analysis of Creative Thinking Ability Based on Self-Regulation in Model Eliciting Activity Learning with Performance Assessment - Susanti, Ely Susanti; Waluya, S. B.; Masrukan, Masrukan (Unnes Journal of Mathematics Education Research, 2020)
This research aims to describe creative thinking ability seen from self-regulation of the students on Model Eliciting Activities learning (MEAs) with performance assessment. This research was a sequential explanatory. The population was VII grade students of SMP Ibu Kartini Semarang, consisting of four classes. The technique of sampling was purposive sampling. It was selected VII C as experimental group. The subjects were grouped based on self-regulation with high, moderate, and low categories to be interviewed dealing with mathematical creative thinking. The instruments were test and interview. The findings showed that MEAs with performance assessment was qualified well and description of creative mathematics thinking based on self-regulation of the students varied.